PRINCIPAL MANAGERIAL CAPACITY AS A CORRELATE OF TEACHER PRODUCTIVITY IN KWARA STATE SECONDARY SCHOOLS (1989)
In Kwara State and in many other States of the Federation, students’ poor academic performances were usually blamed on poor school management by principals and bad teaching by teachers respectively. The final output in terms of General Certificate of Education or West African School Certificate Examination results had always been used as yardsticks for assessing the failure or success of schools. Critics were not mindful of "the process" to the final output. This study had taken cognisance of the principal managerial process that could lead to high teacher productivity in relation to high academic performance of students. Principal managerial, capacity had been seen as his ability to plan, organize, coordinate, motivate, control , administer, supervise and intervene; while teachers’ productivity had been viewed with teachers’ ability for classroom management, lesson delivery, record keeping, assignment gradings, guidance counseling, extra and co-curricular activities designed for the study were Principal Management Capacity Questionnaire (PMCQ) and Teacher Productivity Questionnaires (TPQ). Eighty (80) schools, 80 principals, 576 teachers and 812 students from 11 of the 12 L.G.As. were sampled. Schools sampled were under the dual Controls of the State Ministry of Education and the Kwara State Education Management Board. Part of the design of the instrument was to assess the amount of "supportive aids" or "reinforcement" given by the two Controlling agencies for principal and teacher proper functioning. A pilot study involving 3 Local Government areas, 10 principals, 100 teachers and 200 students, was carried out to standardize the instruments for validity, and reliability. seven (7) study hypotheses with sub-sections were generated. In analysing the result, One way ANOVA with ‘F’ ratio; ’T’ test and Pearson Product Movement Correlation ’r’ were used. Major findings of the study showed that: 1. Principal Managerial Capacity and teacher productivity were rated significantly high. 2. There was a significant relationship between Principal Managerial Capacity and Teacher Productivity. 3. Academic and social aspects of school goals were perceived significantly high. 4. Relative experience and qualifications were regarded by teachers as necessary pre-requisites for appointing principals. 5. Principals, teachers and students recorded very low ratings for the "supportive aids" or "re-inforcement". 6. Teachers in Government secondary schools were perceived as having higher productivity than those in Board schools. 7. Female teachers’ output were rated lower than males. 8. Students’ ratings of their teachers were found to be umbrella" of control table, reliable and valid and could be used in assessing teacher productivity. The findings suggested that principals were capable of high managerial capacity, while teachers we read judged as capable of high, productivity, but were handicapped by lack of "supportive aids" like funding, equipment, staffing, classroom/laboratory adequacy and visits from Board and Ministry. The dual nature of school control was another area identified as creating disharmony among principals and teachers of Government and Board Schools. In view of the findings, there might be need for further research into male/female teacher productivity the effects of the dual' control of secondary schools to determine the suitability or otherwise of bringing all schools under "one umbrella" of control. The research findings are only applicable to Kwara State secondary schools in view of the scope and the design of the study.